MODELS OF ENERGY DISTRIBUTION IN SPECTRUM OF SAKURAFS OBJECT - Pavlenko, Ya.; Yakovina, L.; Duerbeck, H. W. (Одеські астрономічні публікації, 2017)
Theoretical energy distributions in a spectrum of Sakurai's object (SO) are calculated for a grid of hydrogen-deficient and carbon-rich model atmospheres of Teff = 5000-6200 K and log g= 0.0-1.0. Model atmospheres of SO are computed by the technique of opacity sampling with account of atomic and molecular absorption. Theoretical energy distributions are compared with the spectrum of SO in April 1997 at λλ 300 - 1000 nm. We show, that (1) theoretical energy distributions agree well at least qualitatively with the observed ones and depend strongly on Teff ; (2) an absorption by the C3 and CN bands is dominated in visible and near IR region of the SO spectrum, an atomic absorption becomes important in UV and blue region. We estimate for SO Teff ≈ 5500K and its interstellar reddening Eb-v = 0.70 for April, 1997.